2021
DOI: 10.1016/j.ajpath.2021.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Human Type II Taste Cells Express Angiotensin-Converting Enzyme 2 and Are Infected by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)

Abstract: Chemosensory changes are well-reported symptoms of SARS-CoV-2 infection. The virus targets cells for entry by binding of its spike protein to cell-surface angiotensin-converting enzyme- 2 (ACE2). It was not known whether ACE2 is expressed on taste receptor cells (TRCs) nor if TRCs are infected directly. Using an in-situ hybridization (ISH) probe and an antibody specific to ACE2, ACE2 is present on a subpopulation of TRCs, namely, Type II cells in taste buds in taste papillae. Fungiform p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 49 publications
1
66
0
2
Order By: Relevance
“…As potential endocrine organs, fungiform papillae may provide us with a new window into human physiology that is easily accessible and observable, one that could be utilized in biopsy for further testing and examination. Along those lines, we have recently reported that SARS-CoV-2 infect taste receptor cells in taste buds of biopsied fungiform papillae [ 56 ]. With all these relevant areas of research in mind, we have developed an in vivo model and mechanistic studies are currently underway to study age-related and SARS-CoV-2 related taste loss or changes.…”
Section: Discussionmentioning
confidence: 99%
“…As potential endocrine organs, fungiform papillae may provide us with a new window into human physiology that is easily accessible and observable, one that could be utilized in biopsy for further testing and examination. Along those lines, we have recently reported that SARS-CoV-2 infect taste receptor cells in taste buds of biopsied fungiform papillae [ 56 ]. With all these relevant areas of research in mind, we have developed an in vivo model and mechanistic studies are currently underway to study age-related and SARS-CoV-2 related taste loss or changes.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A substantial body of evidence has demonstrated the effect of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on olfaction, 3 although few observations exist regarding a direct involvement of the virus in the pathogenesis of gustatory impairment. 4 While the correlation between self-reported olfactory function and psychophysical tests has been extensively analyzed, showing poor agreement between the 2 types of evaluation, no robust data exist concerning the gustatory function. 5 To establish whether psychophysical tests confirm a self-reported alteration of taste, we assessed a series of patients selfreporting a persistent distorted perception of basic tastes after COVID-19 using a comprehensive gustatory and olfactory psychophysical evaluation.…”
mentioning
confidence: 99%
“…It has been shown that the taste buds and salivary glands have a high number of ACE2 receptors ( Doyle et al, 2021 ; Song et al, 2020 ). Furthermore, the essential role of the renin-angiotensin-aldosterone system (RAAS) in the perception of flavors has been confirmed previously.…”
Section: Ageusia Pathophysiologymentioning
confidence: 99%